2020
DOI: 10.1002/jmr.2845
|View full text |Cite
|
Sign up to set email alerts
|

Epitope specificity of two anti‐morphine monoclonal antibodies: In vitro and in silico studies

Abstract: Monoclonal antibodies (mAbs) against morphine are important in the development of immunotherapeutic and diagnostic methods for the treatment and prevention of drug addiction. By the surface plasmon resonance (SPR) and enzyme immunoassay techniques, we characterized two previously obtained mAbs 3K11 and 6G1 and showed their ability to recognize free morphine and morphine‐containing antigens in different ways because of the epitope specificity thereof. Using the defined amino acid sequences, we obtained three‐di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 32 publications
0
2
0
2
Order By: Relevance
“…Respecto a las constantes de disociación KD, recopiladas también en la Tabla 1, el mAB comercial evaluado por Eldefrawi (2000), anti-MOR mostró el menor valor con 0.23 nM, por lo tanto se considera el de mayor afinidad de los 14 mABs comparados. Los mABs de Glasel (1983), Trofimov et al (2020, y Berzina et al (2016) también fueron de alta afinidad con valores de 5 -30, 61 y 123 nM, respectivamente, así como el scFv M86 de Matsukizono (112.6 nM;Matzukizono et al, 2013).…”
Section: Afinidad Y Límites De Detección De Los Mabsunclassified
See 1 more Smart Citation
“…Respecto a las constantes de disociación KD, recopiladas también en la Tabla 1, el mAB comercial evaluado por Eldefrawi (2000), anti-MOR mostró el menor valor con 0.23 nM, por lo tanto se considera el de mayor afinidad de los 14 mABs comparados. Los mABs de Glasel (1983), Trofimov et al (2020, y Berzina et al (2016) también fueron de alta afinidad con valores de 5 -30, 61 y 123 nM, respectivamente, así como el scFv M86 de Matsukizono (112.6 nM;Matzukizono et al, 2013).…”
Section: Afinidad Y Límites De Detección De Los Mabsunclassified
“…Los mABs 6G1 y 3K11 reconocen diferentes fragmentos de la molécula de morfina y son epítopos específicos, lo que les confiere diversas propiedades de afinidad dado que existen diferencias importantes en la constitución química de las regiones determinantes de complementariedad de los dominios variables. 3K11 se asocia tres veces más rápido e interactúa más eficientemente con morfina que el 6G1, lo que se atribuye a que los inmunógenos utilizados para su generación son dos conjugados diferentes (M3-BSA y M6-BSA) en los que la morfina se expuso de maneras diferentes (Trofimov et al, 2020).…”
Section: Estudios Para La Generación De Conocimiento Centrados En Aná...unclassified
“…Therefore, the stability of haptens is also one of the key factors that cannot be ignored in the process. Trofimov et al [ 65 ] obtained two morphine derivatives, 6-hemisuccinyl and 3-O-carboxymethyl esters, and their antibodies. The results showed that antibodies derived from 3-O-carboxymethyl interacted with morphine more effectively than 6-hemisuccinyl.…”
Section: Synthesis and Identification Of Antigenmentioning
confidence: 99%
“…This correlated with the data on the differences in the epitope specificity of these antibodies obtained experimentally by surface plasmon resonance and an immunoenzyme assay. Subsequently, accounting for the obtained data, it is possible to construct humanized anti-morphine antibodies that can be used for therapeutic purposes [57].…”
Section: Monoclonal Antibodies As Tools To Study Biological Molecules and Intermolecular Interactionsmentioning
confidence: 99%